Ethnic differences in the prevalence of peripheral arterial disease: a systematic review and meta-analysis. (3rd April 2017) - Vitalis, Antonios; Lip, Gregory Y. H.; Kay, Mark; Vohra, Rajiv K.; Shantsila, Alena
ABSTRACT: Background : Previous studies have demonstrated higher rates of peripheral arterial disease (PAD) in blacks and lower in Asians compared to whites. The aim of this study is to undertake a comprehensive review of literature on ethnic differences in the epidemiology of PAD. Methods : A systemic review and meta-analysis included studies reporting PAD prevalence in general or diabetic populations, and comparing PAD prevalence in ethnic groups. Results : Mean prevalence of PAD in general population for whites, blacks and Asians was 3.5%, 6.7% and 3.7% respectively. Meta-analysis demonstrated higher prevalence of PAD in blacks (p < 0.001) and lower amongst Asians (p < 0.001), compared to whites. In diabetic population, the mean prevalence of PAD for whites, blacks, east Asians and south Asians was 17%, 25.3%, 13.5% and 7.6% respectively. In diabetic population, south Asians had a lower PAD prevalence (p < 0.001) compared to whites; there was no significant difference between blacks and whites. Overall females have higher PAD rates, in general (3.8% vs 3.2%; p < 0.001) and in diabetic population (13.7% vs 10%; p < 0.001). Conclusion : Blacks are vulnerable to PAD, in contrast to Asians who have lower prevalence of PAD when compared to whites. Further research is needed in order to identify the factors that generate this difference.